2018
DOI: 10.1111/iere.12369
|View full text |Cite
|
Sign up to set email alerts
|

Market Economies With an Endogenous Social Division of Labor

Abstract: I consider a general equilibrium model of a competitive market economy in which production is conducted through an endogenous social division of labor. I represent economic decision makers as “consumer–producers,” who consume as well as produce commodities. In this approach, the emergence of a nontrivial social division of labor is guided by Increasing Returns to Specialization (IRSpec) in production. Under IRSpec, I show existence of competitive equilibria, the two fundamental theorems of welfare economics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…We show below that these results can naturally be extended to the setting of an economy with an endogenous social division of labour and collective good provision. These insights build on the results established by Gilles (2018a), which, in turn, extended the theorems from Schmeidler (1972) and Vind (1972) to the realm of continuum economies with an endogenous social division of labor.…”
Section: Note That ∫mentioning
confidence: 60%
See 4 more Smart Citations
“…We show below that these results can naturally be extended to the setting of an economy with an endogenous social division of labour and collective good provision. These insights build on the results established by Gilles (2018a), which, in turn, extended the theorems from Schmeidler (1972) and Vind (1972) to the realm of continuum economies with an endogenous social division of labor.…”
Section: Note That ∫mentioning
confidence: 60%
“…blocking coalitions by devising conditions under which the theorems of Schmeidler (1972) and Vind (1972) hold in the framework developed here. Gilles (2018a) showed that both of these results extend unconditionally to continuum economies with an endogenous social division of labour. Here, in the context of collective good provision through a social division of labor, we show that the extension of Schmeidler's result that any non-σ -Core allocation can be blocked by an arbitrarily small coalition, applies in our framework.…”
mentioning
confidence: 77%
See 3 more Smart Citations